- Anatomi Daun Varietas Belimbing (Averrhoa carambola L.) Lokal di Taman Buah Mekarsari Bogor: Leaf Anatomy of Local Variety Starfruit (Averrhoa carambola L.) at Mekarsari Fruit Garden, Bogor - Mardhatillah, Tila; Dorly, .; Ratna Djuita, Nina (Departemen Biologi, Institut Pertanian Bogor, 2022)
Sweet star fruit (Averrhoa carambola L., belimbing manis) is one of Indonesia’s most popular fruit plants. Anatomically, the characters of the local sweet star fruit of Mekar Sari Fruit Garden are not widely known, so this study aims to observe the anatomical structure of the leaves. The materials used were star fruit leaves of varieties Demak Jingga, Demak Kapur, Demak Kunir, Welahan, and Wulan. The leaves of star fruit varieties were made microscopic preparations in paradermal incisions using the whole mount method and transverse incisions using the paraffin method. The observation result of the paradermal incision of sweet star fruit leaves showed that the type of epidermal cell wall is straight and shallow grooved. The leaf stomata of five sweet star fruit varieties were paracytic. The calculation of the index value, size and density of stomata varied between varieties. The highest stomata density and index were found in the Welahan variety. The results of the transverse incision of sweet starfruit leaves showed that the five local sweet star fruit varieties have mesophyll tissue of the dorsiventral type. Wulan variety has leaves and mesophyll tissue which tends to be thicker than other varieties.